2018
DOI: 10.1002/mp.12964
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Deep learning based MRAC using rapid ultrashort echo time imaging

Abstract: The proposed MRAC method utilizing deep learning with transfer learning and an efficient dRHE acquisition enables reliable PET quantitation with accurate and rapid pseudo CT generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 52 publications
0
66
0
Order By: Relevance
“…Although the applied U‐Net is widely accepted for mapping image contrast and texture as a results of efficient convolutional encoding and decoding design, successfully translation among different anatomy might still require further design of the generator architecture tailored for handling both contrast translation and geometric transformation. In addition, translating image contrasts among different imaging modalities would be useful in applications such as PET/MR attenuation correction, where there is the need to generate synthetic CT images from MR images for photon attenuation calculation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the applied U‐Net is widely accepted for mapping image contrast and texture as a results of efficient convolutional encoding and decoding design, successfully translation among different anatomy might still require further design of the generator architecture tailored for handling both contrast translation and geometric transformation. In addition, translating image contrasts among different imaging modalities would be useful in applications such as PET/MR attenuation correction, where there is the need to generate synthetic CT images from MR images for photon attenuation calculation …”
Section: Discussionmentioning
confidence: 99%
“…In addition, translating image contrasts among different imaging modalities would be useful in applications such as PET/MR attenuation correction, where there is the need to generate synthetic CT images from MR images for photon attenuation calculation. 63,64 In the current study, the use of adversarial training and cycle consistency regularization as key techniques in the CycleGAN framework was proven to be effective to learn mutually correlated image features with unpaired data in the medical image domain. The adversarial learning ensures the translated images falling into the same data distribution of the target images; the cycle consistency prevents the degeneracy of the adversarial process from generating hallucinated image features.…”
mentioning
confidence: 89%
“…Inspired by the network design in Ref., we utilized the deep convolutional encoder‐decoder network structure shown in Fig. , which is capable of mapping pixel‐wise image intensity from MRI to CT in multiple image scales.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, three‐discrete labels were assigned to soft tissue, air and bone in the generated pseudo CTs that delivered accurate PET/MR attenuation correction with significantly reduced error in reconstructed PET images compared with existing segmentation‐based and atlas‐based methods . In one recent study from the same group, the deep learning approach was applied in combination with an advanced UTE sequence, which achieved reliable and accurate tissue identification for bone in PET/MR attenuation correction in brain imaging . Another recent study demonstrated excellent performance utilizing deep learning generated pseudo CTs for PET/MR attenuation correction in pelvis…”
Section: Introductionmentioning
confidence: 99%
“…We previously used a convolutional encoder-decoder (CED) network for PET/MR attenuation correction in the brain, where contrast-enhanced T1-weighted MR images were used as network inputs to achieve reconstructed PET errors of ∼1% in the brain ( 17 ). We also evaluated the same CED network but with a UTE image as input and using transfer learning to initialize the network weights ( 18 ). This method achieved even better results, with PET errors in the brain generally <1%.…”
Section: Introductionmentioning
confidence: 99%